Reallocation: How new forms arise from contact. Issue 8 (11th August 2022) - Font‐Santiago, Cristopher; Johnson, Mirva; Salmons, Joseph
Abstract: In the last 35 years, 'reallocation' has come to be widely used to describe how structural linguistic features in contact settings may remain as part of a new language variety and take on new functions as sociolinguistic variables rather than be lost over time, as is typically expected in koineization contexts. Classic examples involve originally regional differences that come to carry social, grammatical, or stylistic rather than regional meanings. We define and illustrate reallocation and then explore how it has been used in different ways and applied to various contact settings. Along the way, we also put reallocation into the context of notions like focussing and accommodation, and observe a shift from looking at dialect contact to language contact as a trigger of reallocation. Reallocation increasingly connects with enregisterment, and we consider these notions in cultural as well as strictly linguistic terms. We conclude briefly with paths for future investigation.